PENGARUH PENERAPAN METODE INTERVAL TRAINNING TERHADAP PENINGKATAN VO2MAX PEMAIN SEPAK BOLA - Suherman, Dias; Mubarrok, Mochamad Zakky; Agustin, Nur Mahfuzah (STKIP Melawi, 2025)
Abstract: This study aims to determine the effect of the application of the interval training method on the increase in VO2Max of football players. The research method used in this study is experimental.Â The research design used is